The Right of Access to Justice: Judicial Discourse in Singapore and Malaysia - CHAN, Gary (Institutional Knowledge at Singapore Management University, 2007)
This is an essay on judicial discourse in Singapore and Malaysia pertaining to the nature and scope of the right of access to justice, including access to justice for the poor. We will examine the statements and pronouncements by the Singapore and Malaysia judiciary in case precedents and extra-judicial statements. Some of the issues explored include the legal status of this right of access to justice (namely, whether it is a right enshrined in the constitution or merely a right derived from the common law and whether it is qualified by economic and other interests) and the associated rights of legal representation, legal aid and contingency fees.